2021
DOI: 10.1016/j.molp.2021.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Tonoplast-associated calcium signaling regulates manganese homeostasis in Arabidopsis

Abstract: Manganese (Mn) is an essential micronutrient in plants. However, excessive Mn absorption in acidic and waterlogged soils can lead to Mn toxicity. Despite their essential roles in Mn homeostasis, transcriptional and post-transcriptional modifications of Mn transporters remain poorly understood. Here, we demonstrated that high-Mn stress induces an obvious Ca 2+ signature in Arabidopsis. We identified four calcium-dependent protein kinases, CPK4/5/6/11, that interact with the tonoplast-localized Mn and iron (Fe) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 62 publications
(111 reference statements)
1
42
0
Order By: Relevance
“…Preventing the interference of pathogens from the outside is the prerequisite for healthy growth of plants. Moreover, calcium can promote the growth of root hairs ( Zhang et al, 2021 ). In our study, these calcium-binding genes showed high expression characteristics in roots, indicating that plants with vigorous roots could absorb more nutrients and thus contribute to the accumulation of nutrients by the aboveground leaves, flowers, and pods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preventing the interference of pathogens from the outside is the prerequisite for healthy growth of plants. Moreover, calcium can promote the growth of root hairs ( Zhang et al, 2021 ). In our study, these calcium-binding genes showed high expression characteristics in roots, indicating that plants with vigorous roots could absorb more nutrients and thus contribute to the accumulation of nutrients by the aboveground leaves, flowers, and pods.…”
Section: Discussionmentioning
confidence: 99%
“…The high level of ABA in the kernels or pods can affect the abortion of young ovaries by inhibiting cell division ( Dembinska et al, 1992 ; Setter and Flannigan, 2001 ; Liu et al, 2003 ). Calcium is an essential nutrient element in the process of plant growth and development, which is mainly transported from the roots to aboveground leaves through the xylem ( Zhang et al, 2021 ). A lack of calcium caused empty pods in peanut ( Yang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell type-specific targeting and function may be brought about by essential interacting proteins only present in the respective cell types. One class of interacting proteins are protein kinases, and the regulation of MTP8 by phosphorylation has recently been shown(Zhang et al 2021). It still needs to be established if such potential mechanisms regulate MTP8 in Arabidopsis seeds.…”
mentioning
confidence: 99%
“…For construction of pull-down vectors, the full-length ORFs of ROP6 and the truncated PHT1 genes (PHT1;1-C 504-524AA , PHT1;4-C 504-534AA ) were amplified and subcloned into the pMAL-C2X and pGEX4T-1 vectors, respectively. The pull-down assay was performed as described (Zhang et al, 2021). ROP6 activity assay was performed as previously described (Han et al, 2018).…”
Section: Pull-down Assaymentioning
confidence: 99%